Pelatihan“Tehnik Demo Tool SHOPEE Auto Follow-Exrush.com dan Teknik Iklan Berbayar” - Marlena; Eni Widhajati (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Increasing human resources through the Shopee Auto Follow-Exrush.com Demo Tool Technique Training and Paid Advertising Techniques will greatly assist UMKM actors in promoting and marketing their business. This technique will assist business actors in gaining more followers so that market expansion expectations can be achieved. From the existing problems, the solution that will be given is to provide training related to the problem as a problem solving solution. This activity is intended for business actors (UMKM), carried out at PT. Antik Prosperous Village, District Campurdarat Tulungagung. This training activity can provide knowledge to business actors to increase followers, understand auto follow-exrush.com in e-commerce and how to develop business in the digital market. This activity will be sustainable by providing assistance to business actors (UMKM to monitor the extent to which the results of the training are applied in daily activities and the benchmark for the success of this training is an increase in performance through market expansion and increased turnover of each business actor.